The Aftercare Survey: Assessment and intervention practices after brain tumor surgery in Europe - Sierpowska, Joanna; Rofes, Adrià; Dahlslätt, Kristoffer; Mandonnet, Emmanuel; Ter Laan, Mark; Połczyńska, Monika; Hamer, Philip De Witt; Halaj, Matej; Spena, Giannantonio; Meling, Torstein R; Motomura, Kazuya; Reyes, Andrés Felipe; et al. (Neuro-oncology practice, 2022)
Background: People with gliomas need specialized neurosurgical, neuro-oncological, psycho-oncological, and neuropsychological care. The role of language and cognitive recovery and rehabilitation in patients' well-being and resumption of work is crucial, but there are no clear guidelines for the ideal timing and character of assessments and interventions. The goal of the present work was to describe representative (neuro)psychological practices implemented after brain surgery in Europe. Methods: An online survey was addressed to professionals working with individuals after brain surgery. We inquired about the assessments and interventions and the involvement of caregivers. Additionally, we asked about recommendations for an ideal assessment and intervention plan. Results: Thirty-eight European centers completed the survey. Thirty of them offered at least one postsurgical (neuro)psychological assessment, mainly for language and cognition, especially during the early recovery stage and at long term. Twenty-eight of the participating centers offered postsurgical therapies. Patients who stand the highest chances of being included in evaluation and therapy postsurgically are those who underwent awake brain surgery, harbored a low-grade glioma, or showed poor recovery. Nearly half of the respondents offer support programs to caregivers, and all teams recommend them. Treatments differed between those offered to individuals with low-grade glioma vs those with high-grade glioma. The figure of caregiver is not yet fully recognized in the recovery phase. Conclusion: We stress the need for more complete rehabilitation plans, including the emotional and health-related aspects of recovery. In respondents' opinions, assessment and rehabilitation plans should also be individually tailored and goal-directed (eg, professional reinsertion).